(untitled) (Inovasi, 2019)
This study aims to analyze and identify the leading sub-sectors in the agriculture, forestry and fishing sectors which are priority sub-sectors to be developed. The variables used in this study are a gross regional domestic product (GRDP) in the agriculture sector of Serdang Bedagei Regency and Sumatera Utara Province. The analytical method used in this research is location question analysis (LQ) and shift share (SS). The results of the LQ analysis show that the agriculture, forestry and fishing sectors that are superior are the food crop sub-sector, the livestock sub-sector, and the fisheries sub-sector. The results of the shift-share analysis show that the annual horticultural crop sub-sector, the forestry and logging sub-sector, and the fisheries sub-sector have high competitiveness and have the potential to increase economic growth in Serdang Bedagei Regency. Keywords: agriculture, forestry and fishing sector, location quetiont, shift share